Hold Your Fire! Influence of Female Legislators on Gun Legislation in the US - Rajeev K. Goel; Michael A. Nelson (Center for Economic Studies and ifo Institute (CESifo), 2023)
Objective This paper considers the influence of female legislators on gun legislation across US states. Females have behavioral differences from males and likely different exposure to gun-related violence. Method Using data from 1991-2020, we econometrically estimate the drivers of gun legislation across US states. The dependent variables are alternately the total number of gun laws enacted, and 5-year differences in gun laws. Results We find that female legislators in state houses significantly increase the supply of gun laws. Female senators, on the other hand, were no different from their male counterparts. In other results, states with greater population density had more gun laws, while economic prosperity, race, and the elderly population did not generally have significant effects. Finally, when special interest groups, involving gun ownership, mass shooting episodes, and states with a uniform executive are considered, mass shootings and a uniform executive increase laws, while gun owners have the opposite effect. These findings show significance when 5-year differences in gun laws are used. Conclusions Our findings suggest that, when it comes to gun legislation and female legislator representation, it matters which chamber of the legislature females are elected to. Furthermore, different interest groups can significantly bear upon gun legislation.
Keywords: J16; K10; 330; gun control; gun laws; gender; firearms; legislatures; mass shootings; gun ownership